2021
DOI: 10.21203/rs.3.rs-535561/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-Cov-2 Clearance in Term of Cycle Threshold (Ct) During First Two Waves of COVID-19 in Pakistan: A Phenomenon of Delayed Viral Clearance Post- Corticosteroid Treatment.

Abstract: SARS-CoV-2 is recently emerged virus, which caused millions of deaths, all over the world. To tackle COVID-19 pandemic, there is an utmost need for in-depth analysis of viral replication. We aimed to examine viral load in SARS-CoV-2 patients during first two waves of COVID-19 in Pakistan. 225,615 suspected subjects from 75 different regions of Pakistan were selected in the study. SARS-CoV-2 RNAs were detected via real time PCR. During first wave (period of June-July, 2020) of COVID-19 the prevalence of SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…21 A study in Pakistan revealed that the majority of the population in the second wave of COVID-19 consumed corticosteroids like dexamethasone as an early treatment of SARS-CoV-2 which resulted in delayed viral clearance. 22 This may also explain the CAM outbreak in the country following the second wave. 12 Another plausible factor is that mucormycosis is complex to diagnose in its early stages and requires aggressive diagnostic strategies, posing great challenges for physicians.…”
Section: Circumstancewhat Went Down?mentioning
confidence: 98%
“…21 A study in Pakistan revealed that the majority of the population in the second wave of COVID-19 consumed corticosteroids like dexamethasone as an early treatment of SARS-CoV-2 which resulted in delayed viral clearance. 22 This may also explain the CAM outbreak in the country following the second wave. 12 Another plausible factor is that mucormycosis is complex to diagnose in its early stages and requires aggressive diagnostic strategies, posing great challenges for physicians.…”
Section: Circumstancewhat Went Down?mentioning
confidence: 98%
“…Furthermore, it was reported that an increasing majority of COVID-19 patients took corticosteroid medications especially during the second COVID-19 wave in Pakistan, which explains the recent increment in mucormycosis cases in the country. 9 Additionally, severe COVID-19 disease leads to increased levels of pro-inflammatory markers, including IL-1, IL-6 and tumor necrosis alpha, and decreased levels of CD4 interferon-gamma, CD4 and CD8 cells; which augments the chances of microbial infections including mucormycosis. Usage of low-quality industrial-grade oxygen cylinders, unclean and humid environment of the hospital facility, tap water in humidifiers and antibiotic overuse may also trigger the mucormycosis infection.…”
mentioning
confidence: 99%